2020
DOI: 10.3390/jmmp4010018
|View full text |Cite
|
Sign up to set email alerts
|

Wear in Hot Stamping by Partition Heating

Abstract: Hot stamping by partition heating of Al–Si coated boron steel sheets is currently utilized to produce parts of the car body-in-white with tailored microstructural and mechanical characteristics. This paper investigates the evolution of the Al–Si coating and its tribological and wear performances in the case of direct heating at the process temperatures of 700 °C, 800 °C, and 900 °C, skipping the preliminary austenitization as it may happen in the case of tailored tempered parts production. A specifically desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, studies from Venema et al [8] and Ghiotti et al [9] revealed, that both coating systems cannot withstand the alternating thermo-mechanical load conditions during the combined forming and quenching step. Consequently, excessive tool wear appears within short production periods, which negatively impacts the workpiece quality and the tool lifetime [10]. Moreover, the application of conventional lubricant systems is not possible during hot stamping, since blank temperatures above 800 • C occur.…”
Section: Hot Stamping Of Ultra High-strength Steelmentioning
confidence: 99%
“…However, studies from Venema et al [8] and Ghiotti et al [9] revealed, that both coating systems cannot withstand the alternating thermo-mechanical load conditions during the combined forming and quenching step. Consequently, excessive tool wear appears within short production periods, which negatively impacts the workpiece quality and the tool lifetime [10]. Moreover, the application of conventional lubricant systems is not possible during hot stamping, since blank temperatures above 800 • C occur.…”
Section: Hot Stamping Of Ultra High-strength Steelmentioning
confidence: 99%
“…The friction coefficient under hot/warm stamping conditions is critical to describing the contact conditions at the tool-workpiece interface [8], as this affects the drawability of the material and the springback of the formed component [9]. It has been found that the friction coefficient decreased with increasing temperature, which is typically evaluated by either pin-on-disc/strip or drawing tests [10][11][12].…”
Section: Introductionmentioning
confidence: 99%